Evaluación de las especies lemna minor L. (lenteja de agua) y eichhornia crassipes M. (Jacinto de agua) en remoción de materia orgánica. - Tuesta Flores, Nayti Vanessa (2016)
At the present thesis they were employed with Lemna minor L. and Eichhornia crassipes M. water plants from July until October, 2014, cultivated in fish farms fluent in Moyobamba city, this study seeks to improve more the quality of the effluent one using the water plants, realizing a previous treatment before there being spilt to a body recipient (Gully), expiring with Maximum Permissible limits of water un load. A study was realizad using floating water plants (Lemna minor L. and Eichhornia crassipes M.) to remo ve biodegradable organic matter in effluents from fish farms taking a pilot plant with two systems of treatment: a system in batch es and a continuous system. The system in batches consisted in the application of Lemna minor L. and Eichhornia crassipes M. aquatic plants using the effluent from fish farms to analyze the purifying effect of the aquatic plants, taking a reactor of control (without planting of plants), and three reactors which functioned as systems by" Shifts", develop with homogeneity in the ponds size (planting in the first pond Lemna minor L. in the second pond Eichhornia crassipes M. and the third pond Lemna minor L. and Eichhornia crassipes M.). The continuous system consisted in a slow stream of 0.71 m3/h of the fish farms effluent crossing ponds with different levels of shallow water, in which the Lemna minor L. and Eichhornia crassipes M. floating aquatic plants were culturad working with a reactor of control (without plants), and three reactors which functioned as "seamless" systems, (planting in the first pond Lemna minor L., in the second pond Eichhornia crassipes M. and the third pond Lemna minor L. and Eichhornia crassipes M.). In both systems in the system in batches and in the continuous system, aquatic plants maintain the conditions of aerobic degradation of organic matter and sediment filtered, thanks to their roots, where it develops an intensa activity of microorganisms. In the investigation course, it was evaluated the growth of aquatic plants especially of its roots which extend down within the water column and the ability to remove biodegradable organic matter, to be carried out by four months the physiochemical analysis between them turbidity, pH, total suspended solids, temperatura, dissolved oxygen, biochemical oxygen demand and Chemical Demand of Oxygen, and then be comparad with the Maximum Permissible Limits for effluents of wastewater treatment plants of domestic or Municipalities ( SUPREME DECREE N°003-2010-MINAM) and in this way see the efficiency of the organic matter removal for each parameter and analyzed system. In the investigation had concluded that the continuous system is much more efficient in the removal of organic matter to the 50% that the system in batches, being more efficient the reactor 04 with Lemna minar L. y Eichhomia crassipes M. aquatic plants, because its roots have the ability to remove the total suspended solids in the effluent of the waters of the fish farms and achieving reproduced plants to 1 00% of the space of the reactors due to the fact that there is continuous movement of water and that makes plants have a better development and greater organic matter removal in the effluent from fish farms. Concluding that aquatic plants Lemna minar L. and Eichhomia crassipes M. comply with the function of removing biodegradable organic matter significantly in the reactors operated in the system in batches and in the continuous system. Key words: water plants, organic matter.